Variáveis de ocupação do solo e microclimas urbanos no período noturno bairro Camobi, Santa Maria - RS - Lazarotto, Gerusa (2015)
Considering the urbanization as factor responsible for climate changes at the local scale, this research has investigated the influence of the environment built in the formation of urban microclimates in Camobi District, Santa Maria City, RS. The climate of the place is humid subtropical, with hot summers and cold winters. The method seeks to analyze the relationship between the occupation of urban land patterns (building density, ground cover and amount of vegetation) and climatic variables (temperature and relative humidity). The approximate calculation of urban variables within the samples was done from aerial photos and field work observation. The climate variables were obtained by data loggers at fixed stations, located in 10 points of the district with different land occupation patterns. The analysis was based on the data nighttime from 3 days in the summer and 3 days in the winter, in 2014.Through qualitative assessment, it was observed the thermal variation among points, according to the different ways of land use. In the statistical analysis, by simple linear regression method, the results have showed, in a few days, significant correlations between the dependent variables (temperature or relative humidity) and independent variables (building density, pavement, covering plant and tree). In general, the results have showed, in the summer and in the winter: positive correlation between pavement and air temperature, negative correlation between covering plant and air temperature, negative correlation between pavement and relative humidity and positive correlation between covering plant and relative humidity. Only in the summer, the results have showed: positive correlation between building density and air temperature, negative correlation between building density and relative humidity, negative correlation between tree and air temperature and positive correlation between tree and relative humidity. Information obtained by the work corroborate with the theory about approach of heat island and show that the variables act in a complex way in the heat exchange in the urban environment. Even so, the results indicate only a tendency, due to the small number of sample sand the analyzed days. The results also indicate the need for more specific studies on the influence of land use for the type of climate in question, focusing on the different forms of spatial configuration related to the building density and tree vegetation. Despite some limitations in the working method and difficulties of measurements in urban areas, the study was able to show that the urbanization of the district causes microclimate changes and therefore must be considered in the design practices and urban planning aimed at environmental quality of cities.